Educating for a Cosmopolitan Ethos in Education: Adapting Expectations to Reality - Persson, Roland S. (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2022)
Cosmopolitanism is an ancient Greek notion which in modern times has found its way into educational practice. It expresses a moral responsibility toward everyone irrespective of cultural background, looks or ability. However, it is an ideology difficult to operationalise and convey in education if the objective is to change learners’ attitudes for the future benefit of mankind. There are several obstacles standing in the way such as concurrent but incompatible value systems, the rise of individual empowerment for global economic growth and most important perhaps, the evolutionary basis of human nature. It is, for example, not possible to encourage competitive behaviour and simultaneously aim at imparting moral values. It is difficult to effectively teach a cosmopolitan mindset, but this is not to say that we should not try. Drawing from the research of multiple disciplines the conclusion of this article is inevitably paradoxical. While the effort to strive for moral cosmopolitanism is a good one, it is also not a one that is entirely possible. We must adjust expectations rather than trying to find miraculous methods by which to enable a better World through general tolerance and acceptance everywhere. Sadly, the latter is not possible. We can at best expect to have a local impact made possible by dialogue.